45. Dosimetric comparison of four radiological techniques for percutaneous ablation of hepatic tumors. (December 2016) - Hadid, L.; Geryes, B. Habib; Roy, J. Le; Costes, C.; Guiu, B.; Correas, J.M.; Seror, O.
Abstract : Introduction: Radiological interventional procedures are increasingly used to treat tumors. It has already proven its efficiency for hepatic tumor ablation using percutaneous needles. Additionally to echography, useful for tumor tracking and needle guidance during the procedure, other X-ray imaging modalities can be used to control needle positioning according to adjacent critical structures. The aim of this study is to evaluate patient dose across three different university hospitals using four different imaging modalities: cone beam CT (CBCT), Computed tomography using helical mode (CT), Computed tomography using dedicated fluoroscopic mode (CT-fluoro) and finally a combination of CT-fluoro and C-arm (CT-fluoro + C-arm). Methods: We included a total of one-hundred and forty-eight (148) procedures. Thirty-four patients were treated with an INNOVA-IGS540 (GEMS) system for CBCT group. One CBCT is performed at the beginning of the procedure to visualize tumors in three dimensions; while a second CBCT is made at the end of the intervention to check the ablation zone. During the procedure, virtual superposition of the target over fluoroscopic images allowed needle positioning. Thirty-four patients were treated with a DISCOVERY-750HD (GEMS) CT without dedicated fluoroscopic mode. Multiple helical acquisitions were made during the procedure: pre-operatively as workup and to locate the tumor; intra-operatively to control needle positioning; and post-operatively to check ablation zones. Forty-nine patients were treated with an optima 660 CT (GEMS) using Smartview fluoroscopic mode (CT-fluoro) for intra-operative needle guidance and positioning. Finally, thirty-one patients were treated with the same optima 660 CT, in combination with an OEC 9900 Elite (GEMS) C-arm. This mobile surgical X-ray system was used for hepatic intra-arterial Lipiodol injection for non-visible tumors under echography or water-soluble contrast CT. Beside Lipiodol injection, intra-operative needle positioning was realized under CT-fluoroscopy guidance. Effective doses were estimated from DLP and DAP using conversion factors. Results: The average maximum diameter of treated tumors was 3.7, 2.7, 1.9 and 1.6 cm for CBCT, CT, CT-fluoro, and CT-fluoro + C-arm, respectively. The median effective dose for pre-operative, intra-operative per needle, and post-operative phases was respectively estimated to 5, 1 and 6 mSv for CBCT; 3, 4 and 3 mSv for CT; 19, 1 and 12 mSv for CT-fluoro; and 32, 3 and 13 mSv for CT-fluoro + C-arm. Conclusions: Compared to CT, CBCT technique delivers lower radiation doses during needle positioning. Regarding global patient dose, CT is still valuable for procedures, especially for those requiring a small number of needles. However, the use of CT-fluoro mode can optimize doses during intra-operative phase. Finally, the use of CT combined with C-arms seems to be the most irradiating modality for patient, but with a possible improvement in tumor visualization.